Severe Reversible Pulmonary Hypertension in Smoldering Multiple Myeloma: Two Cases and Review of the Literature. (1st March 2015) - Feyereisn, Wayne L.; Fenstad, Eric R.; McCully, Robert B.; Lacy, Martha Q.
Abstract : An association between pulmonary hypertension (PH) and POEMS syndrome (characterized by polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes) as well as other plasma cell dyscrasias, including multiple myeloma (MM), has been shown to exist. Recent case reports have identified a reversible form of PH that occurs outside of previously identified etiologies. We report two cases of PH in the setting of smoldering MM (SMM) that resolved with chemotherapy and stem cell transplantation. Although other features were individualized among the cases (dermatomyositis, scleromyxedema), treatment of MM and SMM resulted in a normalization of right ventricular systolic pressure and improvement in right ventricular dysfunction that was previously unresponsive to PH therapies. The magnitude and sustained nature of reversibility in these four cases could offer clues about the pathophysiology and treatment of PH.